Recent advance in infant nutrition: Human milk oligosaccharides - Yu-Jyun Cheng; Chun-Yan Yeung (Pediatrics and Neonatology)
Breast feeding and human milk are the standards for infant feeding and nutrition. Human milk oligosaccharides (HMOs) are the third most abundant solid component in human milk. To date, more than 200 structural different HMOs have been identified and some can be synthesized by the food industry. HMOs are one of the major differences between human milk and formula milk, and current evidence demonstrates their various beneficial effects toward infants' health: acting as anti-adhesive antimicrobials, immune modulators, and intestinal cell response modulators, as well as providing prebiotics effect and neurodevelopment and cognition effects. HMOs compositions vary among mothers, influenced by the stage of lactation, duration of pregnancy and maternal genetic factors. However, there are still some unknown factors affecting the compositions of HMOs and requiring further research for clarification. A combination of preclinical and clinical cohort studies may help to identify whether an individual HMO contributes to disease protection. In recent years, 2′-fucosyllactose (2′-FL) and lacto-N-neotetraose (LNnT) have been approved as food ingredients by official authorities. Infant formulae supplemented with these HMOs are well-tolerated. However, more prospective clinical studies are warranted to elucidate HMOs' significance in infant nutrition. Breast milk feeding remains the best option for infants nutrition and development. Whenever breast milk is not adequate or unavailable, infant formula supplemented with HMOs might be considered as an alternative.